Identifikasi Kesulitan Belajar Mahasiswa pada Mata Kuliah Statistika Selama Masa Pandemi Covid-I9 - Deci Ririen; Dewi Hartika (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
The length of the online learning period in tertiary institutions that has lasted for approximately 10 months has made students uneasy, because the majority of students consider statistics courses to be difficult to understand, especially with the Covid-19 pandemic conditions. The purpose of this study was to determine the factors that caused student learning difficulties in the Statistics course during the Covid-19 pandemic and to determine the dominant factors causing student learning difficulties in the Statistics course during the Covid-19 pandemic. The research subjects were STIE-Indragiri students taking Statistics courses. Instruments of the research method through questionnaires and interviews with research subjects. The results obtained were the factors that made learning difficulties for students in the statistics course during the Covid-19 pandemic, namely the factors themselves, lecturers' factors, environmental factors / parents as well as facilities and infrastructure factors. The most dominant factor affecting student learning difficulties in statistics courses during the Covid-19 pandemic was the infrastructure factor with a TCR value of 64.38%.